Risk Factors for Falls in Adults With Rheumatoid Arthritis: A Prospective Study1. Issue 8 (26th July 2013) - Stanmore, Emma K.; Oldham, Jackie; Skelton, Dawn A.; O'Neill, Terence; Pilling, Mark; Campbell, A. John; Todd, Chris
<x xml:space="preserve">Abstract</x> Objective To investigate the association between potential risk factors and falls in community‐dwelling adults with rheumatoid arthritis (RA). Methods We followed patients for 1 year of followup in a prospective cohort study with monthly falls calendars and telephone calls. Lower extremity muscle strength, postural stability, number of swollen and tender joints, functional status, history of falling, fear of falling, pain, fatigue, medication, and use of steroids were assessed as risk factors for falls. Results A total of 386 women and 173 men with RA (n = 559) ages 18–88 years completed baseline assessments and 535 participants (96%) completed 1‐year followup. Bivariate logistic regression showed that falls risk was not associated with age or sex. Multivariate logistic regression revealed that a history of multiple falls in the previous 12 months was the most significant predictive risk factor (odds ratio [OR] 5.3, 95% confidence interval [95% CI] 2.3–12.3). The most significant modifiable risk factors were swollen and tender lower extremity joints (OR 1.7, 95% CI 1.1–2.7), psychotropic medication (OR 1.8, 95% CI 1.1–3.1), and fatigue (OR 1.13, 95% CI 1.02–1.2). Conclusion Adults with RA are at high risk of falls. In clinical practice, high‐risk fall patients with RA can be identified by asking whether patients have fallen in the past year. Important risk factors highlighted in this study include swollen and tender lower extremity joints, fatigue, and use of psychotropic medications.